2016
DOI: 10.1177/1753193416635803
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area of the ulnar nerve after decompression at the cubital tunnel

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…This study confirms the recent reports of Duetzmann et al 33 in open and endoscopic cubital tunnel release: lower CSA reduction of the ulnar nerve at the elbow seems to be not so strongly associated with clinical improvement, unlike previous studies of the median nerve. [34][35][36] This lack of important reduction in CSA in ulnar nerve decompression is probably related to a irreversible fibrosis rather than a reversible endoneurinal edema in long lasting CuTS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirms the recent reports of Duetzmann et al 33 in open and endoscopic cubital tunnel release: lower CSA reduction of the ulnar nerve at the elbow seems to be not so strongly associated with clinical improvement, unlike previous studies of the median nerve. [34][35][36] This lack of important reduction in CSA in ulnar nerve decompression is probably related to a irreversible fibrosis rather than a reversible endoneurinal edema in long lasting CuTS.…”
Section: Discussionsupporting
confidence: 91%
“…Beekman et al 32 reported in 2004 that the mean values of the ulnar nerve were reduced to only 90% of the pre-operative value at 14 months follow-up. While Duetzmann et al 33 found a CSA reduction to 93% (12.9 mm 2 ± 2.3, paired t-test, P-value < 0.001) of the pre-operative value at 46 months follow-up in 73 patients treated by either endoscopic or open surgical decompression. Although with satisfactory results (54% of excellent results, 22% good, 20% fair and 4% poor) the lack of reduction of CSA might be due to the number of patients with a high severity compression grade in the study of Duetzmann et al 33 In contrast with these results, a greater reduction of the CSA of the median nerve has been reported in carpal tunnel release by Abicalaf et al 34 (6.4 mm 2 ), Vögelin et al 35 (3.2 mm 2 ) and Tas et al 36 (2.3 mm 2 ± 3.4 mm 2 ).…”
Section: Discussionmentioning
confidence: 90%
“…In their study they found a slight reduction in the mean value of the cross-sectional area of the nerve. They draw a conclusion that ultrasound examination seems to be of limited in follow up after surgery [12]. In our investigation we saw higher reduction in cross-sectional area of the ulnar nerve postoperatively.…”
Section: Discussionsupporting
confidence: 50%
“…Like CTS, the EDX community would benefit from a modality that could determine the cause of symptoms that sometimes are present after an ulnar nerve release. The ulnar nerve usually decreases in size after surgery but remains abnormal 25,76 . If a preoperative CSA is available, an increase in size after surgery compared with a baseline value is unusual and could represent recurrent or incompletely decompressed UNE.…”
Section: Specific Conditionsmentioning
confidence: 99%
“…If a preoperative CSA is available, an increase in size after surgery compared with a baseline value is unusual and could represent recurrent or incompletely decompressed UNE. In addition, most studies show that the ulnar nerve size after surgery does not differ significantly between those with good and poor outcomes 25,66,76 . This limits the value of the CSA of the ulnar nerve after surgery when ulnar nerve symptoms are present.…”
Section: Specific Conditionsmentioning
confidence: 99%